A 25-year retrospective analysis of factors influencing success of aluminum treatment for lake restoration. (15th July 2021) - Agstam-Norlin, O.; Lannergård, E.E.; Rydin, E.; Futter, M.N.; Huser, B.J.
Highlights: Aluminum treatment had instant effect on water quality parameters in all study lakes. The success of treatment was explained by e.g. Al dose and binding efficiency. Recommendations are made for properly assessing Al-treatments in the future. Abstract: For more than 50 years, aluminum (Al)-salts have been used with varying degrees of success to inactivate excess mobile phosphorus (P) in lake sediments and restore lake water quality. Here, we analyzed the factors influencing effectiveness and longevity of Al-treatments performed in six Swedish lakes over the past 25 years. Trends in post-treatment measurements of total phosphorus (TP), Chlorophyll a (Chl_a), Secchi disk depth (SD) and internal P loading rates (Li) were analyzed and compared to pre-treatment conditions. All measured water quality parameters improved significantly during at least the first 4 years post-treatment and determination of direct effects of Al-treatment on sediment P release (Li) was possible for three lakes. Improvements in TP (-29 to -80%), Chl_a (-50 to -78%), SD (7 to 121%) and Li (-68 to -94%) were observed. Treatment longevity, determined via decreases in surface water TP after treatment, varied from 7 to >47 years. Lake type, Al dose, and relative watershed area were related to longevity. In addition, greater binding efficiency between Al and P was positively related to treatment longevity, which has not previously been shown. Our findings also demonstrate that adequate, long-term monitoring programs, including proper determination of external loads, are crucial to document the effect of Al-treatment on sediment P release and lake water quality.